Pendidikan Mengatasi Perubahan Iklim berdasarkan Literasi Iklim untuk Pertanian Berkelanjutan di Provinsi Sulawesi Tengah - Solih Alfiandy; Asep Firman Ilahi (Buletin GAW Bariri (BGB), 2023)
The Meteorology, Climatology and Geophysics Agency continues to strive to enhance understanding of climate change and its impact through climate literacy, especially in Central Sulawesi Province. Climate literacy through this program can enchance the understanding of agricultural extension officers, farmers, and flagship farmer groups about climate change and help addres challenges in agriculture. The aim of study is to determine the extent of the increase in the knowledge capacity of Human Resources regarding Climate and Climate Change on agriculture through climate literacy in the Central Sulawesi Province. The literacy methods used include visual education materials, interactive training, and life skills approaches. The results obtained show in 21.24% increase in understanding during the period of the Climate Fields School implementation in Central Sulawesi Province. Local government hope that this climate literacy activity can continue as an effort to enhance the capacity of human resources in agriculture to archive climate – smart agriculture. The BMKG Climate Fields School is a valuable resource for empowering agricultural enthusiasts and achieving sustainable agriculture.